Thru the years to '76 - Bicentennial West Fargo-Riverside History Book Committee; J&M Printing (North Dakota State Library, 1977)
A history of West Fargo, North Dakota including family biographies. 252 pages : illustrations, photographs 26 cm. Jamestown College, graduated in 1931, and taught at Fredonia and Kulm. I went on to graduate work and in 1934 graduated from the Baptist Missionary School in Chicago. I came back to North Dakota, married Walt, and have been a "home missionary" ever since. Walt went to Valley City Teachers College, taught school for one year, and decided he'd rather be a salesman. He worked for the Maytag Washer Company for several years, then for his father. West Fargo was in its infancy then; that is, the south side of Highway No. 10. All of the north side was Armour Company and its people. We felt there was a great future for us, and it has proven to be so. Walt and Frieda Ruff. Sons, Dale and Jack, with dog Ginger in 1946. In 1945 we built our first supermarket for our Red Owl Agency store. We bought a lot on Main Street from Mr. A.P. Martin. The present occupant is the Quality Boneless Beef Co. During the war it was very difficult to obtain building materials, but with the help and planning of our lumber man, Mr. M.E. Pederson, who owned the Farm & Home Lumber, we wee able to put up a very adequate building for a store and a apartment in the back. Lloyd Rogne and Ervin Rogne did the construction. It was West Fargo's first big grocery store. Our biggest problem, as I recall was the eternal mud. There were few sidewalks and often we had to shovel out the gumbo at the end of the day. It was a great day when the parking area in front of the store was paved — no more cars getting stuck out front. We would haul in gravel only to have it sink into the gumbo. It seemed an endless task. In those days many of our customers called in orders and we made deliveries to their home. In 1951 Walt became interested in Dairy Queen. It was a new idea of soft serve ice cream. We met Mr. and Mrs. Carl White and from them purchased the franchise for a Dairy Queen in West Fargo. We also purchased the two lots a block east from Mr. Joe Marlow. On the corner we built the Dairy Queen and on the other lot we built a building for Johnny Leaman's Store. We operated the Red Owl until 1952 when we sold it to Mr. and Mrs. Powers. We hired someone to run the Dairy Queen that summer, and we loaded our two boys. Dale age 15, and Jack age 12, and an extra tire and headed to Alaska via the Alaskan Highway. We spent 3 weeks driving, going as far as 150 miles north of Fairbanks to the end of the road. We spent a few days at Circle Hot Springs near the Arctic Circle, then drove to Anchorage, sold the car there, flew to Kodiak Island, for a summer with Mr. and Mrs. John Wolf, and flew home just in time for school to begin. The next few years were busy summers at the Dairy Queen. The two boys helped while students at West Fargo High and North Dakota State University. Dale graduated in Architectural Engineering and Jack in Electrical Engineering. When Johnny Leaman and his J.L.S.O.S. store moved from West Fargo, we decided to open a Skogmo Clothing Store and sell the Dairy Queen. In 1969, we again sold the business and this time we didn't move a block further east, but decided to retire. We had been 31 years in business on Main Street. The Chamber of Commerce honored us with a dinner and presented us with a plaque for the long standing participation in West Fargo and for active membership in many community activities. We are members of the Community Presbyterian Church, for twenty years I taught Sunday School and Bible school and directed the choir. The Women's Association has always been and still is one of my first choice activities. I am also a member of the Amita Women's Club. Walt has been on the Village Board when S.W. Fargo became a city, and acquired its water and sewer system. He is now on the city assessment board, and maintains an active membership in the Lions Club. We both belong to the Cass County Historical Society and have been active in the development of Bonanzaville, helping whenever we can in the many projects there. When the boys were in school we were active in Cub Scouts, band parents, P.T.A., and all the other school and community activities. One year I directed the high school girls' chorus in a musical play "Miss Caruthers". Our son, Dale, and his wife Lola (Braaten) live in Fargo with their family, Rob, JuLee, Mark and Lisa. Dale is an assoicate with the architectural firm, Foss, 85 Scanned with a Zeutschel Zeta book scanner at 300 dpi. Edited with Multi-Page TIFF Editor.